#### Question

Solve the following quadratic equations by factorization:

`3x^2-2sqrt6x+2=0`

#### Solution

We have been given

`3x^2-2sqrt6x+2=0`

`3x^2-sqrt6x-sqrt6x+2=0`

`sqrt3x(sqrt3x-sqrt2)-sqrt2(sqrt3x-sqrt2)=0`

`(sqrt3x-sqrt2)(sqrt3x-sqrt2)=0`

Therefore,

`sqrt3x-sqrt2 = 0`

`sqrt3x=sqrt2`

`x=sqrt(2/3)`

or,

`sqrt3x-sqrt2 = 0`

`sqrt3x=sqrt2`

`x=sqrt(2/3)`

Hence, `x=sqrt(2/3)` or `x=sqrt(2/3)`

Is there an error in this question or solution?

#### APPEARS IN

Solution Solve the Following Quadratic Equations by Factorization: `3x^2-2sqrt6x+2=0` Concept: Solutions of Quadratic Equations by Factorization.